Parliamentary elections in Britain. (UK : Foreign and Commonwealth Office, 1996)
The electoral system, the campaign, Polling day, political parties, after the general election, elections to the European parliament...
Keywords: Politics; Great Britain; Election; Elections -- Great Britain